Capture, representation, and rendering of 3D audio for virtual and augmented reality - Tashev, Ivan (International Journal on Information Technologies and Security, 2019)
Devices for augmented and virtual reality (AR/VR) find applications in gaming, entertainment, education, design and science. An AR/VR headset consists of a head-mounted display, headphones or loud-speakers, and a computing platform. The spatial audio system plays integral party of achieving the realism. In this article we present an overview of our work on technologies for the 3D audio targeting AR/VR scenarios.